A Need for Investment in Nigerian Crude Oil Refining and Infrastructures: A Panacea to Refined Petroleum Shortages and Economic Growth - Itsekor, Lucky (Archives of Business Research, 2020)
Despite the abundance of occurring natural crude oil resources, Nigeria continually suffers shortages of refined petroleum products, which undermines economic development of the country. The purpose of this multicase study was to explore the strategic role of how investment in petroleum refineries and infrastructures can improve supply and hence mitigate shortages or scarcity of refined petroleum products in the petroleum supply chain and enhance economic development in Nigeria. The research participants comprise of ten senior leaders from two private-sector Nigerian downstream petroleum supply companies located in the Niger Delta region, who had effectively implemented strategies for petroleum supply. The conceptual framework for the study was the resource based view theory. Data were collected through semistructured face-to-face interviews and review of operational and policy documents from the supply or marketing petroleum companies. Data were transcribed, analyzed, and validated through member checking and triangulation. The discoveries indicate the need to establish more refineries, privatize the existing moribund refineries, and build more infrastructures in Nigeria. Findings may be used by petroleum leaders and investors to optimize available crude oil natural resources, and to create investment strategies in the petroleum supply chain, leading to product availability, sustainability, poverty reduction, and economic development in Nigeria.